2013
DOI: 10.1002/ange.201300755
|View full text |Cite
|
Sign up to set email alerts
|

The Stoichiometry of Electroless Silicon Etching in Solutions of V2O5 and HF

Abstract: Wohin mit den Elektronen? Beim stromlosen Ätzen von Silicium zur Bildung von nanokristallinen porösen Si‐Filmen extrahiert das Oxidationsmittel ein Elektron aus dem Si‐Valenzband, um den Ätzvorgang zu initiieren, und ein zweites aus dem Leitungsband, um die H2‐Bildung zu unterdrücken. Diese Entdeckung kippt die klassische Auffassung zur Rolle des Oxidationsmittels; die Stöchiometrie wurde aus den gezeigten UV/Vis‐Spektren abgeleitet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Under this convention, at least one additional oxidant would have to be involved in the silicon oxidation to complete the missing part of the valence transfer. According to the current state of knowledge in the literature, this is attributed to the reduction of hydrogen ions to molecular hydrogen [ 16 , 38 , 39 , 40 , 43 , 49 , 50 , 51 , 52 ] according to the reaction equations formulated in Equations (2) and (4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under this convention, at least one additional oxidant would have to be involved in the silicon oxidation to complete the missing part of the valence transfer. According to the current state of knowledge in the literature, this is attributed to the reduction of hydrogen ions to molecular hydrogen [ 16 , 38 , 39 , 40 , 43 , 49 , 50 , 51 , 52 ] according to the reaction equations formulated in Equations (2) and (4).…”
Section: Resultsmentioning
confidence: 99%
“…According to a prominent theory, there is a kinetically controlled transfer of two electronic holes h v + from the metal cation/metal redox pair Me z+ /Me to the valence band of the silicon (divalent mechanism, Equation (1)) [ 16 , 38 , 39 , 40 ], or in the case of copper deposition, an electron uptake of the metal ions via the conduction band mechanism of silicon [ 11 ]. Furthermore, a twofold electron transfer e c − from the silicon conduction band to the hydrogen ions or other HF species contained in the solution results in the formation of Si 4+ and molecular hydrogen (Equation (2)) [ 16 , 38 , 39 , 40 ]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of por-Si films in Fe 3+ + HF solutions under illumination with a Xe lamp has also been studied (Xu and Adachi 2007). Kolasinski and Barclay (2013a) have demonstrated that the stoichiometry of stain etching is distinct from that of anodic por-Si formation. This occurs because the injection of a conduction band electron in the current doubling step is used to reduce H + to H 2 in anodic etching, whereas this electron is consumed by the oxidant in stain etching.…”
Section: +mentioning
confidence: 99%
“…Silicon dissolution in fluoride-containing electrolytes is primarily driven by the supply of holes in the silicon [42][43][44]. More details on the chemical reactions involved in stain etching can be found in the supplementary information (SI 2).…”
mentioning
confidence: 99%